"There's Always Going to Be Uncertainty": Exploring Undergraduate Student Parents' Sources of Uncertainty and Related Management Practices. (October 2021) - Scharp, Kristina M.; Cooper, R. Amanda; Worwood, Jared V.; Dorrance Hall, Elizabeth
Framed by uncertainty management theory, the present study explores the uncertainty issues and management practices of undergraduate student parents. Results from 40 narrative interviews reveal seven sources of uncertainty, eight management practices, and two uncertainty trade-offs. Findings reveal that having two interrelated identities (student and parent) not only exacerbate some uncertainties but create completely new ones. This intersectionality also holds implications for management practices. Theoretical implications and practical applications are discussed.